Optimization of production layout, production process, and supply of materials to increase work productivity in Saramanta homemade - Setyaningrum, Ratih; Erthamevia, Firlinda Kirana; Febriana, Sofi Dwi; Setyanti, Ananda Viona Islamay (OPSI, 2025)
Saramanta Homemade located in Boja, Kendal is an MSME that produces various cakes. In its production, Saramanta Homemade experiences several obstacles, namely: less than optimal layout; work is done without a work desk, which affects worker he alth and reduces productivity; and decreased profits due to increased costs due to the supply of raw materials. In previous studies, productivity optimization was only focused on layout planning, while this study discusses measuring supply chain performance to increase profits and product design to implementation of designed products. Therefore, researchers use the EFD, SLP, and SCOR methods to solve these problems. The EFD method is used to design an ergonomic work desk with dimensions l = 1610mm, w = 710mm, and h = 1020mm so that it can reduce musculoskeletal complaints as evidenced by a RULA value of 2. The SLP method is used for changing positions between departments, shortening the moving distance by 71%, the total moving time by 50%, and OMH by 47% so that the layout can be optimized through the proposed layout design using Blocplan software. SCM performance measurement with SCOR of 63.83% (average). As well as alternative proposals for selecting suppliers from Semarang, shipping costs of Rp50,000, Emina cheese brand of Rp45,000/kg, and the addition of 4 workers so that expenses are reduced by 5.8%, profits increase by 58.1%, and cash-to-cash cycle time becomes 31% shorter.